PENGUATAN EKOSISTEM INDUSTRI HALAL MELALUI PENGEMBANGAN SUMBER DAYA MANUSIA (SDM), RISET DAN PENGEMBANGAN (R&D) - Handry Cahyopy (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2023)
The readiness of human resources (HR) through research and development (R&D) is an important component to strengthening the halal industry ecosystem so that it can compete on a global scale. This study aims to find out the constructive portrait of strengthening the halal industry ecosystem through human resource development, research and development (R&D) in Indonesia. This type of research is qualitative research which is a literature review (literature review). Sources of data come from secondary data obtained through articles, documentation books, the internet, as well as data published by institutions that have trusted credibility in Indonesia. Based on the search, there are four recommended strategies to strengthen the halal industry ecosystem through human resource development, research and development (R&D), namely: 1) Increasing the effectiveness and involvement of halal industry players in improving the quality of human resources, 2) Improving the quality and quantity of human resources in educational institutions based on sharia economy, 3) Construction of a halal center for the development of integrated halal industry, 4) Development of human resources and research-based regulatory framework for halal industrial products. The four main programs (quick-wins) that are suggested are, 1) an Accelerated HR certification program for those who will/are currently working in industries that are within the scope of Islamic economics, 2) an Accelerated curriculum standardization program for Islamic economic education institutions, especially at the undergraduate and graduate levels. vocational education, 3) the Creation of Islamic economic data centers and mapping of tertiary institutions that specialize in developing Islamic economic research, 4) Increasing the quality and quantity of halal industry research.